The Effect of Grit on Work Engagement Among Generation Z Employees in Samarinda City - Amelia Raranditha; Desita Dyah Damayanti; Indo Sennang (Journal of Social Research, 2026)
This study addresses the increasing challenges faced by Generation Z employees in adapting to dynamic work environments, where psychological resilience and sustained engagement are essential for optimal performance. In Samarinda City, the dominance of Generation Z in the workforce highlights the importance of understanding internal factors that influence work engagement. This study aims to examine the effect of grit on work engagement among Generation Z employees. A quantitative inferential research design was employed, involving 111 respondents selected through purposive sampling based on the Lemeshow formula. Data were collected using validated psychological scales measuring grit and work engagement, and analyzed using simple linear regression with SPSS. The results indicate that grit has a positive and statistically significant effect on work engagement (t = 3.080; p < 0.05), although its contribution is relatively small (R² = 0.08). This finding suggests that while perseverance and consistency in achieving long-term goals enhance employee engagement, other factors also play a substantial role. In conclusion, grit serves as an important psychological resource that supports work engagement among Generation Z employees, but it is not the sole determinant. Future research is recommended to explore additional variables influencing work engagement